Diseño de un modelo de negocio para la creación de una herramienta basada en el aprendizaje activo e inteligencia artificial que fortalezca el proceso de aprendizaje - enseñanza. (2021)
This project will be developed in the city of Bogotá DC and will be specifically delimited to higher education institutions (IES) which do not have high quality accreditation in their industrial engineering program, the purpose of this project is to develop a model of business which is viable for the creation of a tool based on artificial intelligence and active learning. Said evaluation of the business model will begin by carrying out a diagnostic analysis of the sector in which we find ourselves, this in order to know how it is said and have a much broader picture of the pros and cons that we will find when establishing the model. of business there, secondly we will carry out a market study in the market niche which we established previously, this will give us a more accurate vision of the way in which to penetrate said market niche and create possible marketing strategies to make the most effective business model.